Pengembangan Media Ular Tangga Berbasis Genially untuk Meningkatkan Pemahaman Keragaman Budaya di Sekolah Dasar - Septiana, Erin Bela; Widodo, Susilo Tri (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – Observations revealed that students' low interest in learning, exacerbated by ineffective media, hindered their understanding and retention of material. To address this, an innovative strategy integrating play-based learning through digital snake and ladder media is proposed.Method – This research is included in the type of Research and Development. The procedure for developing snakes and ladders media based on genial uses a development model developed by Sugiyono with ten stages, namely potential and problems, data collection, product design, design validation, design revision, initial trial, product revision, usage trial, product revision, and mass production. Findings – The findings of this study indicate a media expert validation score of 85.93% with a very feasible category, and material experts obtained a score of 90.38% with a very feasible category, from the results of the two validators an average of 88.15% was obtained with a very feasible achievement. The results of the response of grade V teachers of SDN Ngaliyan 05 in the initial trial with subjects of 6 students with an average score of 95.9% with a very feasible category, while the response of students in the trial of use with subjects of 23 students with an average score of 85.43% with a very feasible category. The results of the effectiveness of the snake and ladder media based on genially obtained an average pretest score of 60,43 and a posttest of 82.39 with an n-gain test result of 0.55 with a moderate category. Research Implications – The limited time available in the learning process often becomes an obstacle in achieving in-depth understanding, causing this research to only cover a small part of the topic that should be studied so that the results obtained do not fully describe a comprehensive picture of the phenomenon being studied.